Analysis of Financial-Economic Indicators of Startups - Melkumyan, Zaruhi; Mirzoyan, Soghomon; Hovsepyan, Meri; Nazaryan, Samvel; Minasyan, Davit («Տնտեսագետ» հրատ․)
This article delves into the financial-economic dynamics of international startups, with a focus on three prominent companies: Monday, Bolt, and Airbnb. The study examines changes in assets, funding sources, and financial results from 2018 to 2022, revealing divergent trends. Bolt has experienced significant asset growth, primarily driven by borrowing, while Monday has shown increased financial independence. Despite negative net profits, these startups prioritize long-term strategies over short-term profitability, as evidenced by positive gross profits. Furthermore, the article extends its financial-economic indicator analysis to Armenian startups, specifically Krisp and Picsart, examining their from 2021 to 2022. Krisp has demonstrated a reduction in assets alongside a decrease in liabilities, leading to improved financial independence. In contrast, Picsart has exhibited asset growth driven by internal resources, resulting in enhanced return on assets. Overall, this research highlights that startups strategically invest in expansion, anticipating long-term gains and increased market share value, despite short-term losses. The findings provide valuable insights into the financial dynamics
Keywords: Education; Innovation